Reinvention of health applications with Iot : challenges and solutions - Ambikapathy; Shobana R.; Logavani; Dharmasa (Boca Raton : CRC Press, 2022)
"Discusses IoT in healthcare and how it enables interoperability, machine-to-machine communication, information exchange, and data movement. Covers how healthcare service delivery automates patient care with the help of mobility solutions, new technologies, and next-gen healthcare facilities with challenges faced and suggested solutions prescribed. This book presents the latest applications of IoT in healthcare along with challenges and solutions. It looks at a comparison of advanced technologies such as Deep Learning, Machine Learning, and AI and explores the ways they can be applied to sensed data to improve prediction and decision-making in smart health services. It focuses on society 5.0 technologies and illustrates how they can improve society and the transformation of IoT in healthcare facilities to support patient independence. Case studies are included for applications such as smart eyewear, smart jackets, and smart beds. The book will also go into detail on wearable technologies and how they can communicate patient information to doctors in medical emergencies. The target audiences for this edited volume is researchers, practitioners, students, as well as key stakeholders involved in and working on healthcare engineering solutions"--
Includes bibliographical references and index.
Keywords: Mechanical Engineering